Moralitas Hakim di Indonesia dalam Mewujudkan Keadilan menurut Perspektif Aristoteles - Rivaldianto, Muhammad; Salman, Muhammad; Nurali, Sintia; Maharani, Yolanda; Ramadias, Tegar Riffael (Nusantara: Jurnal Pendidikan, Seni, Sains dan Sosial Humaniora, 2023)
In achieving justice, a judge is required to behave professionally, but professionalism here is not only about obeying existing rules and implementing these rules in a case at hand. However, in achieving justice, it is necessary to have a good judge’s morality relationship, because what is in a law is not always the same as what is faced in reality. In this case, the problem faced is how to apply the morality of judges in Indonesia in realizing justice according to Aristoteles perspective. Of course, with the problems faced, this study aims to determine the morality of judges in Indonesia in realizing justice according to Aristotle’s perspective. To achieve this goal, this research uses a normative juridical approach, which is an approach based on the main legal materials by exploring the principles, concepts and legal theories as well as laws and regulations related to this research. philosophical approach. The philosophical approach is used to examine the thoughts of the characters and reveal the essence of everything that appears. This approach was chosen because the research is a study of the thoughts of figures, namely Aristoteles with his studies discussing the concept of justice. The results of this study are to find out how the morality of judges in Indonesia is, and to know the concept of justice according to Aristoteles. Then the research also explains how the morality of judges in Indonesia in achieving justice according to Aristotle’s perspective.